IDENTIFICATION OF THERAPEUTIC INDEX ED50 AND LD50 USING DIGOXIN AND NaCL IN WHITE RATS (Rattus Norvegicus) - Suryaningsi Umaili (Jurnal Ilmiah dr. Aloei Saboe, 2023)
This research aims to obtain an experimental picture to obtain DE50 and DL50 and understand the concept of therapeutic index and dose response of drugs for white rats (Rattus Novergicus). The research method used is a laboratory experimental method using 4 experimental animals, male white rats inith weight 200 g. Meanwhile, the drug being tested for its therapeutic index is digoxin. In addition to drugs, physiological NaCl was also used as a negative control. The results showed that menunjukkan administration of drug doses to experimental animals, namely white rats (Rattus novergicus),LD50 and ED50 were not obtained because the data were insufficient and after the study, in rat I experienced tremors at minute 11 after being given 5 mL of digoxin solution. Furthermore, the second rat experienced tremor at 9 minutes with 10 mL of digoxin solution. Then the III rats were given 15 mL of digoxin solution and experienced tremors at 4 minutes. Then the IV rats were given 5 mL of physiological NaCl. After that, it was counted at 8 minutes, IV rats experienced tremors.